Book Review: Mosaicos romanos en el espacio rural: Investigación y puesta en valor - Luigi QUATTROCCHI (Journal of Mosaic Research, 2020)
Mosaicos romanos en el espacio rural: Investigación y puesta en valor, Luz Neira Jiménez (ed.), 374 pages, 294 figures colour & black and white. L’ERMA di BRETSCHNEIDER, Hispania Antigua. Serie Arqueologica 10, 2019, € 340,00 ISBN 9788891318909 (printed book), € 272,00 ISBN 9788891318923 (pdf version).